Alinhamento estratégico entre negócio e tecnologia de informação na perspectiva da teoria Ator-Rede: o caso da internet em um banco brasileiro - Santos, Heloísa Mônaco dos (2005)
Business-IT (Information Technology) Strategic Alignment is a complex phenomenon that has been intensively studied for many years. A lot of research has been carried out and it has significantly contributed to the development of the knowledge of this topic. Nevertheless, studies show there are aspects to be explored and point to the Actor-Network Theory as an alternative to focus on the theme Alignment. The present thesis shows the theoretical perspective of the Actor-Network Theory and from an empirical point of view, based on that perspective, studies the process through which the utilization of the Internet has become a reality for a Brazilian bank and has evolved from 1995 to 2005. It also discusses the benefits and contributions of the adoption of said theoretical perspective in the context of Business-IT Strategic Alignment. This study (1) indicates that several actors were involved in the incorporation of the Internet by the bank and are involved in maintaining it as an important technological tool for the institution; several strategies were and are still adopted in order to sustain the relationship between the Internet and the bank, and (2) suggests that the Actor-Network Theory offers a different vision of “alignment”, from the one related to the traditional concept of management, and its perspective on fact analysis represents a tool for managers who seek for Alignment.